Echocardiography and 6-Minute Walk Test for Assessing Disease Progression in Systemic Lupus Erythematosus - Przywara-Chowaniec, Brygida; Dyrcz, Dominika; Beres, Marcin; Harpula, Jan; Nowak, Agnieszka; Tomasik, Andrzej (Cardiology and Cardiovascular Medicine, 2019)
Introduction: Systemic lupus erythematosus is an autoimmune disease characterized by the production of antinuclear and cytoplasmic antibodies that can affect many organs. Cardiovascular diseases occurring in patients with SLE include myocardial infarction, coronary heart disease, stroke, transient cerebral ischemia, or thromboembolic disorders. Early identification of heart dysfunction in SLE is important in determining the course of the disease. Aim of the study: The aim of this study was to show the relationship between the presence of SLE and changes in echocardiographic parameters, in particular LVEF, 6MWT results and complete blood count. We also aimed to show the correlation between disease duration and LVEF. Material and methods: The subjects of this study were patients with SLE. The study results from October 2014 to February 2019 were analyzed. The analysis included 45 patients with SLE, comprising 40 women aged 55.67 ± 11.34 years and 5 men aged 62.6 ± 8.43 years. The study group consisted of patients with an SLE diagnosis and an average disease duration of 12.58 ± 8.18 years. Results: In the echocardiographic study, the left ventricular end-diastolic diameter in the parasternal long-axis view was significantly larger in the SLE group than in the non-SLE group (45.60 ± 6.72 vs. 40.75 ± 6.83 mm, p = 0.0247). In the 6MWT, the distance covered by the SLE group was statistically smaller than that of the non-SLE group (547.86± 87.59 vs. 595.37 ± 78.56 m, p = 0.0472). The disease duration was important in left ventricular systolic dysfunction (r = 0.4516, p = 0.0001). Disease duration correlated with MPV (r = -0.4057, p = 0.0017). Conclusions: Echocardiographic examination may significantly influence t